A Generalized switched inductor cell modular multilevel inverter - Kumar A.; Wang Y.; Raghuram M.; Pilli N.K.; Singh S.K.; Pan X.; Xiong X. (My University, 2025)
An interesting feature of a Z-source inverter is to provide buck-boost ability in a single stage. However, this concept is most popular in the conventional inverters. In a few multilevel inverters (MLIs), Z-source is utilized to have higher gain along with retaining the advantages of an MLI such as better electromagnetic interference compatibility, low harmonic distortion, etc. However, the potential of the Z-source concept is not fully exploited in MLIs. To widen the feasibility of the Z-source concept in the MLI, a modular MLI is considered. In this article, a generalized switched inductor cell is selected as a Z-source network for integration, however, other Z-source networks such as quasi-boost network, quasi-switched boost network, two winding coupled inductor network, three winding coupled inductor network, etc., may be used in place of a switched inductor cell. The quantitative and qualitative analysis is done for the proposed converter in both the continuous current mode and discontinuous current mode. The analysis shows that a higher voltage gain can be achieved in the discontinuous current mode as compared to the continuous current mode. To control the proposed converter, two new modulation techniques are proposed, i.e., full shoot through and upper shoot through/lower shoot through. Finally, the proposed converter is validated experimentally in both the modes and for different modulation techniques. © 1972-2012 IEEE.